Landau Level Broadening in the Three‐Dimensional Topological Insulator Sb2Te3. Issue 11 (18th April 2018) - Storz, Oliver; Sessi, Paolo; Wilfert, Stefan; Dirker, Chris; Bathon, Thomas; Kokh, Konstantin; Tereshchenko, Oleg; Bode, Matthias
Abstract : Topological insulators (TIs) possess an insulating bulk and spin‐momentum‐locked Dirac‐like surface states which are topologically protected from backscattering. This connection between charge and spin currents makes TIs highly attractive for spintronics and quantum computing applications where spin‐encoded information needs to be coherently transmitted and processed with high‐fidelity. However, the physical limits of quantum coherence in TIs have not yet been fundamentally understood. Here we demonstrate by scanning tunneling spectroscopy (STS) measurements at high magnetic fields that the broadening of Landau level (LL) states in Sb2 Te3 exhibit a maximum width at the zeroth LL and monotonously decrease away from the Dirac energy. The weak magnetic field dependence verifies that the spin–orbit‐induced spin texture of topological states effectively protects them from scattering even at the highest achievable magnetic fields. Abstract : Landau levels in the topological insulator Sb2 Te 3 are investigated by scanning tunneling spectroscopy at high magnetic fields. The scanning tunneling microscopy image of an Sb2 Te3 surface created by cleaving is shown on the left. The right image is a schematic representation of the Landau orbits produced by a magnetic field within the Dirac cone together with their experimentally determined dispersion. The slope of the linear relation of E vs. k gives the group velocity v D .